Exciton and phonon dynamics in highly aligned 7-atom wide armchair graphene nanoribbons as seen by time-resolved spontaneous Raman scattering. Issue 37 (18th September 2018) - Zhu, Jingyi; German, Raphael; Senkovskiy, Boris V.; Haberer, Danny; Fischer, Felix R.; Grüneis, Alexander; van Loosdrecht, Paul H. M.
Abstract : Time-resolved spontaneous Raman experiments on 7-AGNRs show the presence of a long lived excitonic dark state together with short and long lived trap states. Abstract : The opening of a band gap in graphene nanoribbons induces novel optical and electronic properties, strongly enhancing their application potential in nanoscale devices. Knowledge of the optical excitations and associated relaxation dynamics are essential for developing and optimizing device designs and functionality. Here we report on the optical excitations and associated relaxation dynamics in surface aligned 7-atom wide armchair graphene nanoribbons as seen by time-resolved spontaneous Stokes and anti-Stokes Raman scattering spectroscopy. On the anti-Stokes side we observe an optically induced increase of the scattering intensity of the Raman active optical phonons which we assign to changes in the optical phonon populations. The optical phonon population decays with a lifetime of ∼2 ps, indicating an efficient optical-acoustic phonon cooling mechanism. On the Stokes side we observe a substantial decrease of the phonon peak intensities which we relate to the dynamics of the optically induced exciton population. The exciton population shows a multi-exponential relaxation on the hundreds of ps time scale and is independent of the excitation intensity, indicating that exciton–exciton annihilation processes are not important and the exsistence of dark and trapped exciton states. Our results shed light on the optically induced phonon and exciton dynamics in surface aligned armchair graphene nanoribbons and demonstrate that time-resolved spontaneous Raman scattering spectroscopy is a powerful method for exploring quasi-particle dynamics in low dimensional materials.